2000
DOI: 10.1016/s0014-5793(00)01629-x
|View full text |Cite
|
Sign up to set email alerts
|

VIP‐derived sequences modified by N‐terminal stearyl moiety induce cell death: the human keratinocyte as a model

Abstract: Vasoactive intestinal peptide (VIP) is a recognized growth factor affecting many cell types. We have previously developed a series of lipophilic VIP analogues containing an N-terminal covalently attached stearyl moiety. The current studies identified stearyl-Nle 17 -VIP and stearyl-Nle 17 -neurotensin 6À11 VIP 7À28 , acting at W WM concentrations, as cytotoxic to human keratinocytes. The core C-terminal active VIP-derived peptide, stearyl-Lys-Lys-Tyr-Leu-NH 2 (St-KKYL-NH 2 ), was identified as being responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…(A) General scheme of cellulose bound synthesis. For the N-terminal dye-labeling TBTU-activation was chosen (Granoth et al, 2000b). After punching out the spots, the dye-labeled peptides were cleaved from the cellulose membrane by mild basic hydrolysis (see Experimental) and tested in cell binding assays.…”
Section: Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…(A) General scheme of cellulose bound synthesis. For the N-terminal dye-labeling TBTU-activation was chosen (Granoth et al, 2000b). After punching out the spots, the dye-labeled peptides were cleaved from the cellulose membrane by mild basic hydrolysis (see Experimental) and tested in cell binding assays.…”
Section: Binding Assaymentioning
confidence: 99%
“…Furthermore, VIP chimera derived from secretin and GRF function as selective VPAC 1 receptor agonists (Gourlet et al, 1997b;Vertongen et al, 1997). In contrast, lipophilic fatty acyl VIP hybrids acts as antagonists (Moody et al, 1997;Gourlet et al, 1998), which inhibit the growth of cancer cell lines (Zia et al, 2000) and induce proliferation of keratinocytes (Granoth et al, 2000a) or cell death (Granoth et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…The deduced protein structure (∼123,562.8 Da) contained nine zinc fingers, a proline-rich region, a nuclear bipartite localization signal, a cellular export and import signals, and a homeobox domain profile, suggesting a transcription factor function, a potential cytoplasmic function, and an extracellular activity (Granoth et al 2000). Further comparative analysis identified an ADNP paralog, KIAA0863, ADNP2 (33% identity and 46% similarity), indicating that these genes belong to a novel protein family with a nine-zinc finger motif followed by a homeobox domain (Zamostiano et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The attachment of fatty acids to peptides like vasoactive intestinal peptide (VIP) leads to the generation of a highly potent and selective VIP analogs. [12][13][14] Such lipopeptides have provided novel tools in drug design for Alzheimer's disease, hyperproliferative skin disorders and various forms of cancer. [12][13][14][15][16][17][18][19][20] Previous studies in our laboratory, have demonstrated that lipophilization of RC-160 with long chain fatty acids improves its GH-inhibitory activity.…”
mentioning
confidence: 99%
“…Unlike sustained release formulations, lipophilization can also impart enhanced receptor selectivity to peptides. [12][13][14] The attachment of fatty acids to peptides like vasoactive intestinal peptide (VIP) leads to the generation of a highly potent and selective VIP analogs. [12][13][14] Such lipopeptides have provided novel tools in drug design for Alzheimer's disease, hyperproliferative skin disorders and various forms of cancer.…”
mentioning
confidence: 99%